Predictive risk factors for patients with cirrhosis undergoing heart surgery - Arif, Rawa; Seppelt, Philipp; Schwill, Simon; Kojic, Dubravka; Ghodsizad, Ali; Ruhparwar, Arjang; Karck, Matthias; Kallenbach, Klaus (The annals of thoracic surgery, 2012)
BACKGROUND: Empiric experiences suggest higher mortality and complication risk for patients with cirrhosis of the liver after cardiac surgery. However, cirrhosis is not considered a risk factor in either the EuroSCORE or The Society of Thoracic Surgeons score. We report a large single-center experience of patients with cirrhosis undergoing cardiac surgery with extracorporeal circulation and aimed to evaluate the severity of cirrhosis as a predictor of outcome. METHODS: During 2001 and 2011, we operated on 109 consecutive patients (average age, 64 years; 82 male) diagnosed for cirrhosis with cardiopulmonary bypass for different indications. Thirty-day mortality and long-term mortality were set as primary study end points. RESULTS: Thirty-day mortality was 26%, and 5-year survival was 19%. Patients categorized as Child-Turcotte-Pugh (CHILD) C (n=6; 67% 30-day survival; 0% 5-year survival) and B (n=30; 60%; 5%) had worse 30-day and 5-year survival compared with patients categorized as CHILD A (n=73; 80%; 25%). For 30-day mortality, preoperative EuroSCORE (p=0.015), model for end-stage liver disease (MELD) score (p=0.006), albumin (p=0.023), total protein (p=0.01), and myocardial infarction (p=0.049) revealed significant differences between survivors and nonsurvivors. Multivariate logistic regression identified only MELD score (odds ratio [OR], 1.12; 95% confidence interval [CI], 1.03 to 1.23; p=0.011) and total protein (OR, 0.97; 95% CI, 0.95 to 1; p=0.049) were connected with increased 30-day mortality. Cox regression analysis revealed EuroSCORE (OR, 1.02; 95% CI, 1.01 to 1.03; p<0.0001) and MELD (OR, 1.06; 95% CI, 1.01 to 1.12; p=0.016) predicting the overall mortality. Receiver operating characteristic analysis indicated significant predictive power of MELD (p=0.001) and EuroSCORE (p=0.027) for 30-day mortality. CONCLUSIONS: Patients with cirrhosis undergoing heart surgery with extracorporeal circulation have a poor prognosis. Several preoperative factors are related to outcome. EuroSCORE and MELD score may help to evaluate operation risk and indication.
Available online 24 August 2012
Gesehen am 30.07.2018